Draft genome of amylolytic actinobacterium, Sinomonas humi MUSC 117(T) isolated from intertidal soil - Ser, H..; Tan, W.S.; Cheng, H.J.; Yin, W.F; Chan, K.G.; Lee, L.H. (2015)
The amylolytic actinobacterium, Sinomonas humi MUSC 117(T) was isolated from intertidal soil from Kuantan, Malaysia. MUSC 117(T) exhibited significant starch hydrolysis activity and was chosen for further analysis. Here we report approximately 4.4 Mbp high quality genome sequence of MUSC 117(T). Availability of the genome sequence will contribute to better understanding for the strain and allow further exploitation of its biotechnological potential. (c) 2015 Elsevier B.V. All rights reserved.